2012
DOI: 10.1111/j.1398-9995.2012.02806.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of clinical trials on traditional Chinese herbal medicine for treatment of persistent allergic rhinitis

Abstract: Background: Chinese herbal medicine (CHM) has been used for the prevention and treatment of persistent allergic rhinitis (PAR), but results are still equivocal. This study was to assess the clinical effectiveness of CHM in patients with PAR. Materials and methods: Databases searched included articles published in the Cochrane library, MEDLINE, EMBASE, China National Knowledge Infrastructure, and Wanfang database from 1999 to 2011. The studies included were randomized controlled trials (RCTs) comparing CHM to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 28 publications
(57 reference statements)
1
30
0
Order By: Relevance
“…Compared to sham acupuncture, acupuncture showed a greater improvement on the symptoms of allergic rhinitis than sublingual immunotherapy . Also, acupuncture showed a larger effect than Chinese herbal medicine when compared to the waitlist group .…”
Section: Discussionmentioning
confidence: 85%
“…Compared to sham acupuncture, acupuncture showed a greater improvement on the symptoms of allergic rhinitis than sublingual immunotherapy . Also, acupuncture showed a larger effect than Chinese herbal medicine when compared to the waitlist group .…”
Section: Discussionmentioning
confidence: 85%
“…Notably, the meta-analysis by Wang et al 10 assessing 7 RCTs suggested that CHM improved total nasal symptom scores as compared with placebo. This discordant finding between the study of Wang et al 10 and ours may be a consequence of significant heterogeneity observed in both studies and differences in the backgrounds of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several clinical studies have evaluated the effects of CHM, such as Yu-ping-feng San (YS), Cure-allergic-rhinitis syrup (CS), fermented red ginseng, or Biminne capsules. 8 9 Wang et al 10 have suggested that CHM therapy is useful for the treatment of nasal symptoms in AR patients, based on the effect of decreased nasal symptoms in patients enrolled in seven randomized controlled trials (RCTs). However, some clinical trials have subsequently provided conflicting data for the potential benefit of CHM for AR, 11 12 Itching and sneezing represent two of the main bothersome symptoms of AR, and activation of the central and peripheral nervous systems plays an important role in the 2 processes.…”
Section: Introductionmentioning
confidence: 99%
“…This guideline also pointed out that Chinese herbal medicine (CHM) has often been utilized for managing AR in clinical practice, although the evidence supporting its efficacy and mechanism of action is uncertain [ 5 ]. As suggested by a systematic review published in 2012, CHM might be more effective than placebo for persistent allergic rhinitis, but a confirmed conclusion could not be drawn since all included studies suffered certain methodological limitations [ 8 ].One CHM formula, Yu ping feng san (YPFS), was recommended by Chinese medicine clinical practice guideline to manage AR despite its classification and severity, but the effective treatment duration is not clear [ 9 ]. YPFS formula contains three key herbs: Astragalus membranaceus ( huang qi ), Rhizoma Atractylodis Macrocephalae ( bai zhu ) and Radix Ledebouriellae Divaricatae ( fang feng ) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%